PS-066 A high-risk drug: intravenous concentrated potassium chloride, how to improve safety and quality of care?. (24th March 2015) - Declaye, C; Sennesael, AL; Vastrade, C; Spinewine, A; Pirlot, C; Hecq, JD
Abstract : Background: In the High Risk Medicines (HRM) field, intravenous potassium chloride (IV KCl) has an important role. Purpose: To assess nursing and medical practices in the management of hypokalaemia, to evaluate the accreditation norms of the hospital and define potential actions to make the use of IV KCl safe and standardised. Material and methods: A first audit of IV KCl prescriptions and administration practices was conducted, based on 33 electronic patient records regarding appropriateness of use (kalaemia during hospitalisation, administration rate, etc.). A second audit based on the "Adverse Drug Event Trigger Tool" was conducted to determine the number of iatrogenic hyperkalaemia events per 100 patients who received sodium or calcium polystyrene sulfonate, Kayexalate, during their hospitalisation. Finally, a list of the applicable measures was written with relevant actions depending on different actors. Results: The first audit indicated that 49% of the IV KCl administrations were inappropriate, 19% were appropriate because of patients' kalaemia and the other 32% also if the patient was unable to tolerate oral route. It is noticed from the second audit that 19% of Kayexalateprescriptions stemmed from iatrogenic hyperkalaemia caused by intravenous or oral KCl. Therefore, we decided to prioritise redaction and publication of internal guidelines about KCl use. Rationalisation of the KCl availability should be the second step to implement. Conclusion: Regarding the results, a key issue relates to the health professionals' training as well as the standardisation of hospital practices. Hypokalaemia and KCl administration management procedures have been validated by the Pharmaceutical and Therapeutic Committee. The availability of the different types of KCl in the Institution will be reviewed. Several improvements can be made in the near future. References: Hemstreet BA, Stolpman N, Badesch DB, et al . Potassium and phosphorus repletion in hospitalized patients: implications for clinical practice and the potential use of healthcare information technology to improve prescribing and patient safety. Curr Med Res Opin 2006;22(12):2449–55 Crop MJ, Hoorn EJ, Lindemans J, et al . Hypokalaemia and subsequent hyperkalaemia in hospitalized patients. Nephrol Dial Transplant 2007;22:3471–7 No conflict of interest.